Influence of Tourism Destination Products and Images on Tourist Visiting Decision to Kota Seribu Sungai Banjarmasin - Devin Cahya Triansya; Beta Budisetyorini (Jurnal Pariwisata Terapan, 2018)
AbstractThe continuous rapidly growth of tourism sector with the tight competition in the field of tourismmakes not all tourist destinations in the world always experience an increase in the number of tourist visits each year. Banjarmasin City, dubbed the “Kota Seribu Sungai” or "City of Thousand Rivers" and is known as the Thousand Rivers tourist destination has experiencedfluctuate number of tourist arrivals and tend to decline. The fluctuate number of tourist arrivalssourced from tourist visiting decisions can be influenced by various factors, including tourism destination productsand image. This study aims to see the effects of tourism destination products consisting of physical products, people, packages, and programsalsothe image of tourism destinations consisting of cognitive image and affective image on tourists visiting decision to the city of Thousand River Banjarmasin. The data obtained were taken by questionnaire to 123 tourists by accidental sampling. The results of the research were analyzed using multiple linear regression with two equations, namely (I) The influence of tourism destination products on tourist visiting decision and (II) The impact of tourism destination image on tourist visiting decision. The resultsfound the positive influence of tourism destination products to thetourist visiting decision of 54.5% and the image of tourism destination on the tourist visiting decision of 53.4% and the rest of 45.5% and 46.6% influenced by other factors not examined. The results of the analysis also showed the effect of tourism destination products variable partially consisting of physical products, packages, and programs have an effect on the decision of tourists while people have no influence. As for the variable image of tourism destinations in partial consisting of cognitive image and affective image affect the decision of tourists visiting to Kota Seribu Sungai Banjarmasin.